Synthesis of high-performance nitrogen-containing porous carbon and adsorption properties towards metal ions. Issue 10 (25th February 2016) - Zhou, Wen-Xia; Hu, Tuo-Ping; Gao, Jian-Feng; Chen, Xi; Ping, Wei-Guang; Wei, Chin-Chuan; An, Fuqiang
Abstract: Waste water containing metal ions is one of the main pollution sources of surface water and groundwater, and must be removed effectively. In this paper, nitrogen-containing porous carbons, the 800KH-H2 O and the 800KH-NH3, were synthesized using sunflower plates as the major carbon source carbonized at 800°C and activated with distilled water and concentrated aqueous ammonia at the same temperature. The porous carbons were characterized by surface area analyzer, Fourier transform infrared, element analysis, and scanning electron microscopy. The adsorption properties of the porous carbons toward metal ions were studied by batch methods. The test results show that the average pore diameter of porous carbon is smaller than 2 nm, and nitrogen-containing chemical groups were formed on its surface. The adsorption capacities of the 800KH-NH3 toward Pb 2+ are as high as 786 mg g −1 due to its developed pore structure and nitrogen-containing chemical groups. The adsorption process could be well described by the intraparticle mass transfer diffusion model and the Langmuir–Freundlich model.